DEVELOPMENT OF THINK PAIR SHARE COOPERATIVE LEARNING TOOLS ASSISTED BY INTERACTIVE MULTIMEDIA IN CLASS VI SDN TANAMERA 1 BANGKALAN - Fachrur Rozie (Universitas Trunojoyo Madura, 2022)
Learning tools are very important to uphold a learning. The learning tools developed in this study were syllabus, lesson plans (RPP), modules, student worksheets (LKS) with the aid of learning multimedia. This study aims to develop learning tools using a Think Pair Share cooperative learning model assisted by multimedia learning to improve the learning outcomes of fourth grade students at SDN Tanamera 1 Bangkalan. The results of this study indicate that: (1) The learning tools reviewed by practitioners scored 77% with a very valid category; (2) The learning tools developed are effective based on the individual scores of students who are above 85% and have increased learning outcomes in the high category; (3) The practicality of learning devices that get a percentage value of 87% with a student response questionnaire that gets 69% in the interesting category. Based on what is described above, it can be concluded that the cooperative learning model of think Pair Share type assisted by multimedia learning to improve student learning outcomes for class VI SDN Tanamera 1 Bangkalan is valid, effective, and practical to use in the learning process.